Political opportunities of the strike movement against the fiscal reform in Costa Rica - Alvarado Abarca, Daniel José (2022)
This article aims to analyze the configuration and characteristics of the Political Opportunities Structure (pos) that the social movement against the tax reform bill faced during 2018. The research is based, primarily, on the use of semi-structured interviews, through 2019, to over fifteen people directly involved to the repertories and dialog processes held during the strike in question. This leads to a scope of how difficult and closed were the institutional mechanisms to receive and handle demands during this series of protests.